Anticipative response analysis for elite boxing sport - Akopyan, A. O.; Telyuk, S. I.; Egorov, M. I.; Kulagina, L. A. (Theory and Practice of Physical Culture, 2018)
Subject to the study were the quantitative characteristics of the gender-specific anticipative responses in modern elite boxing at the pre-season training stage. The study data and analyses made it possible to profile the gender-specific anticipative responses in boxing (men's and women's) and judo (men's) sports versus the training stages and fatigue rates. It was found that the technical/ tactical actions driven by the anticipative responses account for 38.7% in modern elite boxing. The quantitative aspects of the anticipative responses were found dependent on the training stage and fatigue rate. In the sparring-based training stage, 40.6% of the scoring technical actions were found driven by the anticipative responses, with the rate growing up to 47.8% at the pre-season stage. The technical/ tactical performance driven by the anticipative responses was found fatigue dependent, with the scoring actions in the elite men's and women's boxing rated to vary round-to-round as 4.6-7.8-3.8 and 4-3-1, respectively.